The study on the Development of Learn and Earn Project for Tourism and hotel students, Faculty of Economics and Tourism, Souphanouvong University - XAYAVONG, Somkhuan; BOUNTHIDETH, Thepduangchan (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
The issue of creating Lao society values in learning was raised at the 4th Central Party Congress of the 11th term. The purpose of this study is to survey the opinion of students in the department of tourism and hotels on the "learn and earn" project. Comparison of students' self-development before and after supplementary work to create a learn-and-earn program for tourism and hotel students that will provide an excellent opportunity for them to develop their employability skills while also learning and earning some income and experiences from part-time work in the tourism industry. The results of the study found that: 77 students are interested in participating in the program, accounting for 100%. In conclusion, this study demonstrates the need for students to participate in learning and generate income while learning, as well as to see the self-development of students in the profession when self-training is being trained from work, such as glue, is important information in promoting the way for tourism and hotel development projects to become a reality in the future. Guidelines for the development of the Learn and Earn program for tourism and hotel students sectors is to cooperate with the private sector in the implementation of the program, improve the curriculum, cooperate with the Confucius Institute in training Chinese language skills for students, create a system for the project by creating legislation, and arrange for students to study full time for the first year and the second year.